Epigenetic induction of tissue inhibitor of matrix metalloproteinase‐3 by green tea polyphenols in breast cancer cells. Issue 6 (31st January 2014) - Deb, Gauri; Thakur, Vijay S.; Limaye, Anil M.; Gupta, Sanjay
<x xml:space="preserve">Abstract</x> Aberrant epigenetic silencing of the tissue inhibitor of matrix metalloproteinase‐3 (TIMP‐3) gene that negatively regulates matrix metalloproteinases (MMPs) activity has been implicated in the pathogenesis and metastasis of breast cancer. In the present study, we demonstrate that green tea polyphenols (GTP) and its major constituent, epigallocatechin‐3‐gallate (EGCG) mediate epigenetic induction of TIMP‐3 levels and play a key role in suppressing invasiveness and gelatinolytic activity of MMP‐2 and MMP‐9 in breast cancer cells. Treatment of MCF‐7 and MDA‐MB‐231 breast cancer cells with 20 µM EGCG and 10 µg/mL GTP for 72 h significantly induces TIMP‐3 mRNA and protein levels. Interestingly, investigations into the molecular mechanism revealed that TIMP‐3 repression in breast cancer cells is mediated by epigenetic silencing mechanism(s) involving increased activity of the enhancer of zeste homolog 2 (EZH2) and class I histone deacetylases (HDACs), independent of promoter DNA hypermethylation. Treatment of breast cancer cells with GTP and EGCG significantly reduced EZH2 and class I HDAC protein levels. Furthermore, transcriptional activation of TIMP‐3 was found to be associated with decreased EZH2 localization and H3K27 trimethylation enrichment at the TIMP‐3 promoter with a concomitant increase in histone H3K9/18 acetylation. Our findings highlight TIMP‐3 induction as a key epigenetic event modulated by GTPs in restoring the MMP:TIMP balance to delay breast cancer progression and invasion. © 2014 Wiley Periodicals, Inc.